Hubungan Pengetahuan Dan Sikap Dengan Personal Hygiene Penjamah Makanan Pedagang Kaki Lima Di Taman Jayawijaya Mojosongo - Muhammad Kholid Khoirullah; Dwi Astuti (Dinasti Research, 2023)
Food is a basic human need for survival, so it must meet individual nutritional needs and be suitable for consumption. Poor food safety is the main source of foodborne illnesses. Food traders' personal hygiene has a big influence on food safety, so that food ingredients are not contaminated. BPOM stated that in Indonesia there are still many street vendors who do not pay attention to personal hygiene and the cleanliness of their selling places. This research aims to determine the relationship between knowledge and attitudes with personal hygiene among street vendors’ food handlers at Jayawijaya Park Mojosongo. The type of research used is quantitative in the form of an observational survey with a cross-sectional approach with a population of street vendor food handlers in Jayawijaya Park Mojosongo. The sample used in this research was 111 food handlers. The results of the research show that there is a relationship between knowledge and personal hygiene of street vendor food handlers (p-value 0.031) and there is a relationship between attitude and personal hygiene of street vendor food handlers (p-value 0.036). In this research, it was concluded that there is a relationship between knowledge and attitudes with the personal hygiene of street vendor food handlers in Jayawijaya Park, Mojosongo.